AGE AND BODY COMPOSITION OF PHYSICALLY ACTIVE FEMALES - Darinka Korovljev; Milena Mikalački; Nebojša Čokorilo (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2011)
During the process of aging at female population, certain changes in body composition take place. Those changes are inevitable and mainly biologically conditioned (Nassis & Geladas (2003); Heymsfield, Lohman, Wang & Going, 2005). Previous researches confirmed positive effects of regular exercising and programmed exercising on body composition. Promotion of motor and functional abilities, and consequently morphological characteristics, application of appropriate recreational activities, greatly influences "delay" of aging and rules which this process is bringing (Mišigoj-Duraković, 2006). The aim of this research was to establish whether there are statistically significant variances in body composition between the groups of individuals that actively exercise, and in relation to the age. The sample of individuals was made of 49 women in total (30-49 years of age) that actively exercise in the fitness club "World Class", Novi Sad. The individuals were grouped in two sub-samples, in relation to the age. The first sub-sample was made of individuals of 30-39 years of age (N=21), and the second sub-sample of individuals of 40-49 years of age (N=28). Application of t test for independent samples established statistically significant variances between pairs of groups in variables Body weight, Fat mass and Body mass index (p<0,05).